AB0756 COMPARATIVE CHANGE IN QUALITY OF LIFE MEASURES IN PRECLINICAL AND ESTABLISHED PSORIATIC ARTHRITIS PATIENTSUNDER SECUKINUMAB TREATMENT. DATA DERIVED FROM THE PROSPECTIVE OPEN LABEL PSARTROS STUDY. (June 2019) - Kampylafka, Eleni; Englbrecht, Matthias; Tascilar, Koray; Lerchen, Veronika; Linz, Christina; Kleyer, Arnd; Simon, David; Rech, Jürgen; Schett, Georg; Hueber, Axel
Abstract : Background: Psoriasis (PsO) and psoriatic arthritis (PsA) differentially impact patients' quality of life (QoL) due to pain, mental changes in the context of chronic inflammation and impaired physical function. Effective anti-inflammatory therapy has shown to be effective to improve QoL in PsO and PsA patients. However, the impact of ant-inflammatory therapy on QoL may be different in the earliest stages of PsA as compared to established disease. Objectives: To perform a detailed comparative investigation of the effect of interleukin (IL)-17 inhibition with 300 mg secukinumab (SEC) on QoL in patients with very early PsA/pre-PsA and established PsA. Methods: Patients from the IVEPsA study (1) on very early PsA/pre-PsA (N=20) and the PSARTROS (2) study on established PsA (N=20) were longitudinally assessed for SF-36, DLQI, PsAID and HAQ-DI at baseline and after 4, 12 and 24 weeks. All patients received SEC treatment; 19/20 pre-PsA patients and 17/20 established PsA patients completed the study. Changes from baseline values were evaluated using linear mixed effects models adjusted for baseline values of each scale, gender, age and disease duration, and plotted as model coefficients and respective 95% confidence intervals that represent adjusted mean absolute improvement from baseline. Scale signs were inverted as necessary to ease interpretability. Further subgroup analysis was conducted using Mann-Whitney. Results: Significant and rapid improvements were observed in both pre-PsA and established PsA treated with SEC with regard to pain (SF-36 bodily pain, BP), general health perception (GH), dermatology quality of life index (DLQI) and PsA impact of disease (PsAID), as well as in the SF-36 component scores (mental component score of SF-36, MCS and physical component score of SF-36, PCS). Physical function- oriented instruments like SF-36 physical functioning (PF), role limitation due to physical problem (RP) and HAQ-DI were preferentially affected in established PsA group due to the higher functional burden of disease ( Figure ). There were more differences with respect to the course of QoL improvements through week 12 and 24, as established PsA patients showed an incremental improvement in SF-36 BP, PF and GH from week 12 to 24 while most of the responses plateaued in the pre-PsA group. Furthermore, established PsA patients who achieved minimal disease activity showed a significantly higher improvement in PsAID, HAQ-DI, SF-36 PF, RP and BP (all p < 0.05). Conclusion: Pain, mental health, general health perception and impact of disease rapidly improve in both very early PsA/pre-PsA and established PsA patients treated with SEC. These data support the concept that very early treatment of PsA leads to significant improvement in QoL with the additional benefit of prevention of bone damage as previously shown (1, 2). References: [1] OP0305 Disease interception in psoriasis patients with subclinical joint inflammation by interleukin 17 inhibition with secukinumab – data from a prospective open label study. Kampylafka et al, aRD June 2018, Volume 77, Suppl. 2 [2] Resolution of synovitis and arrest of catabolic and anabolic bone changes in patients with psoriatic arthritis by IL-17A blockade with secukinumab: results from the prospective PSARTROS study. Kampylafka et al, arthritis Res ther. 2018Jul27;20(1):153 Acknowledgement: This study was supported by an unrestricted grant from Novartis. Disclosure of interests: Eleni Kampylafka: None declared, Matthias Englbrecht Grant/research support from: Roche Pharma aG, Chugai Pharma Europe Ltd., Consultant for: Roche Pharma aG, Chugai Pharma Europe Ltd., abbVie Deutschland GmbH & Co. KG, Celgene GmbH, Lilly Deutschland GmbH, Speakers bureau: Roche Pharma aG, Chugai Pharma Europe Ltd., abbVie Deutschland GmbH & Co. KG, Celgene GmbH, Lilly Deutschland GmbH, Koray Tascilar: None declared, Veronika Lerchen: None declared, Christina Linz: None declared, arnd Kleyer Grant/research support from: Lilly, Consultant for: Lilly, Speakers bureau: abbvie, David Simon Grant/research support from: Novartis, Consultant for: Lilly, Speakers bureau: Janssen, Jürgen Rech Grant/research support from: Bristol-Myers Squibb and Celgene (greater than 10, 000), Consultant for: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi aventis, and UCB (in total more than 10, 000), Speakers bureau: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi aventis, and UCB (in total more than 10, 000), Georg Schett: None declared, axel Hueber Grant/research support from: Novartis, Pfizer, Consultant for: Lilly, Speakers bureau: Lilly, Novartis, Janssen, abbvie